STUDIES ON VAMPIROLEPIS PASSERINA SP. NOV (CESTODA: HYMENOLEPIDIDAE RAILLIET ET HENRY, 1909) FROM PASSER DOMESTICUS - SANJAY SHAMRAO NANWARE,; R. M. DHONDGE,; D. B. BHURE, (The Bioscan, 2011)
The present investigation deals with a new species of the genus Vampirolepis Spassky, 1954 collected from the intestines of Passer domesticus from Mukhed, Dist. Nanded (M. S.) India. The Vamperolepis passerine Sp. Nov. comes closer to all the known species of the genus Vamperolepis in general topography of organ but differs due to having scolex distinctly marked off form strobila, which is oval to rounded in shape narrow at anterior side while broad at posterior side. Rostellum armed, oval to rounded. Rostellar hooks 10 in numbers, arranged in a single circle. Suckers four in number, oval to rounded, arranged in a line. Neck long. Mature proglottids 8-9 times broader than long. Testes are three in numbers. Cirrus pouch elongated, cirrus thin, with the cirrus pouch. Vas deferens is small, coiled tube. Genital pore medium, oval, marginally placed, unilateral. Vagina posterior to cirrus pouch. Ovary compact, in the central part of proglottids. Ootype compact. Vitelline gland post ovarian in position.